The influence of soil plasticity on the seismic performance of bridge piers on caisson foundations. Issue 118 (March 2019) - Gaudio, D.; Rampello, S.
Abstract: This paper investigates the role of soil plasticity on the seismic performance of bridge piers founded on cylindrical caissons through a numerical study where the geometrical and mechanical properties of the caisson and the pier, as well as the weight of the deck, are varied. Numerical models of the soil-caisson-pier-deck systems are subjected to six real acceleration time histories differing in frequency content, strong-motion duration and intensity. Three-dimensional coupled dynamic analyses are carried out in the time domain in terms of effective stresses, assuming an undrained response for the foundation soils. The studied systems are designed to be characterised by the same safety factors under static vertical loads, to evaluate the seismic performance of different systems endowed with similar mobilised shear strength, and by a low pseudo-static factor of safety to promote the activation of plastic mechanisms during seismic shaking. To reproduce the initial state of stress around the caissons, the effects induced by the construction stages are also simulated in the analyses through a simplified procedure. Seismic performance of the systems is evaluated comparing the maximum and the permanent deck drift ratios with corresponding threshold values related to ultimate limit states. It is shown that seismic performance is strongly related to the ratio between the fundamental periods of the flexible-base system and the soil, as well as to the strong motion duration. The range of systems and input properties for which soil plasticity is significant is identified, thus avoiding excessive overestimates of earthquake-induced displacements and inertial forces on the superstructure. Highlights: Soil plasticity can reduce substantially inertial forces acting on superstructure. Influence of earthquake strong-motion duration is crucial for seismic performance. Even accounting for soil plasticity seismic performance worsens at resonance. Linear viscous-elastic models provide reliable results for flexible structures.